2021
DOI: 10.3389/fonc.2021.697143
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Preventive and Therapeutic Potential of Banana and Its Bioactive Constituents: A Systematic, Comprehensive, and Mechanistic Review

Abstract: BackgroundThe banana (Musa spp.) plant produces elongated and edible fruit. The two main parthenocarpic species of banana are Musa accuminata Colla and Musa balbisiana Colla. There are several health-promoting and disease-preventing effects of Musa accuminata Colla, which are attributed to its important bioactive compounds, including phenolics, carotenoids, biogenic amines, phytosterols, and volatile oils, found in the stem, fruit, pseudostem, leaf, flower, sap, inner trunk, root, and inner core. Banana posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 90 publications
0
25
0
Order By: Relevance
“…These naturallyoccurring phytochemicals are also utilized in the discovery and development of anticancer drugs [5,6]. Emerging preclinical and clinical data shows that bioactive food components contain enormous cancer-preventive and anticancer therapeutic potential due to their unique ability to impact various cancer hallmarks, namely sustained proliferation, cell death resistance, energy metabolism, immune surveillance evasion, inflammation, invasion, angiogenesis, and metastasis, by modulating a plethora of oncogenic and oncosuppressive signaling pathways [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These naturallyoccurring phytochemicals are also utilized in the discovery and development of anticancer drugs [5,6]. Emerging preclinical and clinical data shows that bioactive food components contain enormous cancer-preventive and anticancer therapeutic potential due to their unique ability to impact various cancer hallmarks, namely sustained proliferation, cell death resistance, energy metabolism, immune surveillance evasion, inflammation, invasion, angiogenesis, and metastasis, by modulating a plethora of oncogenic and oncosuppressive signaling pathways [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have identified many of these bioactive compounds, such as carotenoids (β-carotene), flavonoids, phenolics, biogenic amines, vitamins A, B, C, and E, and phytosterols [8,84,153,154]. Extracts from different parts of banana fruit and plants were shown to elicit effective protection against oxidative damage to cells and different human diseases triggered by these deleterious events, notably different forms of cancer (reviewed in [155]). These effects are possibly associated with the existence of specific phytoconstituents in banana plants and fruit, including ferulic acid, protocatechualdehyde, 2-pentanone, 4epicyclomusalenone, cycloeucalenol acetate, and chlorogenic acid, which have been shown to exhibit therapeutic cancer-preventing and anticancer abilities (reviewed in [155]).…”
Section: Bananamentioning
confidence: 99%
“…Extracts from different parts of banana fruit and plants were shown to elicit effective protection against oxidative damage to cells and different human diseases triggered by these deleterious events, notably different forms of cancer (reviewed in [155]). These effects are possibly associated with the existence of specific phytoconstituents in banana plants and fruit, including ferulic acid, protocatechualdehyde, 2-pentanone, 4epicyclomusalenone, cycloeucalenol acetate, and chlorogenic acid, which have been shown to exhibit therapeutic cancer-preventing and anticancer abilities (reviewed in [155]). These bioactive compounds have been widely shown to have many positive effects on human health and banana has an effective antioxidant capacity higher than many berries [156].…”
Section: Bananamentioning
confidence: 99%
See 1 more Smart Citation
“…BanLec is one of the most potent anti-viral lectins, but also recognizes bacteria with high-mannose type structures [19,20]. This makes BanLec very interesting as a very potent anti-infective agent with additional immune modulatory capacities [20][21][22][23]. Further information about the intervention with the immune system is needed to understand respective processes.…”
Section: Introductionmentioning
confidence: 99%